Study of circumstances surrounding death in hospitalized paeditric patients in Hospital Universiti Sains Malaysia - Hassan, Amanil 'Ula (2017)
Introduction Childhood mortality is generally recognized as the indicator to monitor child health and wellbeing in a population and it is an overall assessment of country development. The leading causes of death in infants are related to congenital anomalies, chromosomal abnormalities, and prematurity whereas unintentional injuries are the main cause of death in children and adolescent. Children who die in hospital widely differ in age range and clinical presentations. Cases with complex chronic conditions are expected to have a longer hospital stay and requiring interventions in comparison with cases that present acutely. Many studies indicate that mortality is related to several factors, such as time, day, and the source of admission. Poor quality of care is shown to deteriorate at weekends as compared to weekdays. Objectives To describe the circumstances surrounding deaths of hospitalized children in Universiti Sains Malaysia Hospital (HUSM) which includes the demographic and clinical characteristic of children who died in HUSM and to determine the factors associated with the mortality. Methodology This study is a case control study conducted using data from 5 year period (from January 2009 till December 2013). The information was obtained from medical records. For descriptive statistics the categorical variables are expressed as proportions. The differences between groups were evaluated using Chi square and Fisher Exact test for categorical data. Statistical analyses conducted using Multiple Logistic Regression to assess the association of independent effects towards outcome (pediatric mortality).Results A total of 279 cases were enrolled in this study with 139 cases belongs to ‘cases’ group and 140 cases were grouped as ‘control’. Children (aged 1 year to 14 years old) are the predominant group. Majority of patients were Malays (96.8%), followed by Chinese (2.5%) and other ethnic group (Siamese) (0.7%). In general, the common symptom was respiratory illness (30.5%), followed by fever (28.3%), gastrointestinal symptoms (14%), trauma cases (14%) and neurological cases (13%) (p value 0.006). Among the cases with mortality, 88% received treatment urgently (within 4 hours), and 11% of them received their first treatment after 4 to 8 hours. Majority of the cases happened during off hour period (75%) and the remaining of them died during working hours. Those patients who were admitted without any co morbidities were less likely to associate with pediatric mortality and children with co morbidities are 3 times higher risk of death (OR 2.9, 95% CI 1.43, 6.04, p value 0.003). Majority of the patients admitted to HUSM were reviewed by the specialist (77.4%). Early treatment administration has shown to reduce the risk of mortality (OR 0.9, 95% CI 0.04, 0.97, p value 0.048). Conclusion The study found that some of the results were comparable with other previous studies. It is very crucial to identify the factors associate with the risk of pediatric mortality thus in order to improve the care and management of pediatric patients.